Error‐related brain activity associated with obsessive–compulsive symptoms in youth. Issue 4 (14th March 2023) - Becker, Hannah; Liu, Yanni; Hanna, Gregory L.; Bilek, Emily; Block, Stefanie Russman; Hardee, Jillian E.; Heitzeg, Mary M.; Pagliaccio, David; Marsh, Rachel; Fitzgerald, Kate D.
Abstract: Background: Subclinical obsessive–compulsive symptoms (OCS) are common in children, and increase risk for later onset of obsessive–compulsive disorder (OCD). In pediatric patients with OCD, neuroimaging research implicates altered neural mechanisms for error‐processing, but whether abnormal brain response occurs with subclinical OCS remains poorly understood. Methods: Using functional magnetic resonance imaging (fMRI), 113 youth (8–18 years; 45 female) from a community sample were scanned during an error‐eliciting Go/No‐Go task. OCS were assessed dimensionally using the obsessive–compulsive subscale of the Child Behavior Checklist. The association between OCS scores and error‐related brain activity was examined at the whole‐brain level. Results: Lower OCS scores associated with stronger response to errors in dorsal anterior cingulate cortex (dACC), caudate, putamen, thalamus, and occipital cortex. Additionally, lower OCS related to higher capacity for inhibitory control, as indexed by greater accuracy on No‐Go trials during fMRI scanning. The relationship between lower OCS and better accuracy on No‐Go trials was mediated by greater error‐related dACC activity. Conclusions: The inverse relationship between OCS and error‐related activity in the dACC and extended cortical–striatal–thalamic circuitry may index an adaptive process by which subclinical OCS are minimized in youth. Further, these results identify an observable pattern of brain activity that tracks with subclinical OCS severity. Understanding the link between neural networks for error processing and the normal to abnormal range of OCS may pave the way for brain‐based strategies to identify children who are more likely to develop OCD and enable the targeting of preventive strategies to reduce risk. Abstract : Graphical Abstract: This fMRI study examines the association of error‐related brain activity and dimensionally measured obsessive–compulsive symptoms (OCS) in a community sample of youth. Results showed that lower OCS was associated with greater error‐related activity of the dorsal anterior cingulate cortex (dACC), caudate, putamen and thalamus, as well as better task performance. This finding provides new information about error‐related brain activity in youth with OCS and sheds light on neural markers that might be relevant for the later development of OCD pathology.